Counseling on Maintenance of Irrigation Canals in Trucuk Village Klaten Regency Central Java - Suryo Handoyo; Herman Susila; Sumina Sumina; Erni Mulyandari (CV. Ridwan Publisher, 2023)
The study aims to find out maintenance of irrigation Trucuk Village. Trucuk, is an area in Klaten Regency, which mostly consists of rice fields. The rice fields have been around for a long time and still exist today. The cause of existence of these rice fields can still survive because the Trucuk area and its surroundings still get rice field irrigation from banners or rivers. Water to irrigate the rice fields is channeled through permanent and semi-permanent ditches. Care and maintenance are needed to maintain the function of the ditch as a means to drain water. Some of the factors that can reduce the performance of the ditch include damage to the body of the ditch, illegal water taking, waste disposal, and lack of infrastructure to control the flow of water. After carrying out counseling to parties related to the existence of waterways in the village of Trucuk Klaten, it is hoped that the continuity of the water flow and the sustainability of agriculture in the rice fields can run normally. So that socio-economic life in the Trucuk Klaten area and its surroundings can run normally.